The existence of positive solutions for the singular two-point boundary value problem - Niu, Yanmin; Yan, Baoqiang (Topological Methods in Nonlinear Analysis, 2017)
In this paper, we consider the following boundary value problem: cases ((-u’(t))^n)’=nt^n-1f(u(t)) &for 0< t< 1, u’(0)=0,u(1)=0, cases % where n> 1. Using the fixed point theory on a cone and approximation technique, we obtain the existence of positive solutions in which f may be singular at u=0 or f may be sign-changing.